Pengaruh Kebijakan Moneter dan fiskal Islam terrhadap Kesenjangan di Indonesia - Hafizhah, Nur Zakiya; Hikmah, Lailatul; Rusgianto, Sulistya (Universitas Negeri Surabaya, 2024)
Monetary policy and fiscal policy are two important policies in maintaining the economy, especially in maintaining the gap in Indonesia. This study aims to determine the effect of Islamic monetary policy, Islamic fiscal policy, unemployment, and inflation on inequality in Indonesia in the short and long term. The method used in this study is a quantitative method with the Vector Error Correction Model (VECM) analysis technique with time series data from 2011 Q1 to 2022 Q4 taken from the central statistical agency and Indonesian financial and economic statistics. The results of this study indicate that Islamic monetary policy in the short and long term has no effect on inequality, Islamic fiscal policy variables in the short term have not been able to overcome the gap while in the long term fiscal policy is able to overcome the gap, inflation and unemployment have no influence in the short term but have a long-term influence on inequality in Indonesia the higher inflation and unemployment will increase the gap.